2021
DOI: 10.1002/jhet.4345
|View full text |Cite
|
Sign up to set email alerts
|

Introducing new method for the synthesis of polycyclic compounds containing [1,3]dithiine derivatives, with anticancer and antibacterial activities against common bacterial strains between aquatic and human

Abstract: In this study, glycerol:potassium carbonate used as a green deep eutectic solvent, for synthesis of polycyclic compounds containing [1,3]dithiine derivatives. The antimicrobial properties of the derivatives against Lactococcus garvieae and Edwardsiella tarda were tested as bacterial strains between aquatic and human based on the minimum inhibitory concentration (MIC), the minimum lethal concentration (MBC) and inhibition zone diameter (IZD).In addition to antimicrobial properties, cytotoxicity testing was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…the cells were treated with concentrations of 6.25 μM/ml, 12.5 μM/ml, 25 μM/ml, 75 μM/ml, 150 μM/ml, and 300 μM/ml of Y-MOF and pyrazolopyranopyrimidines derivatives for 48 h. After 48 h, the media from the well were removed and added 150 μL of fresh media plus 50 μL of MTT solutions (prepared as 2 mg/ml in PBS) and for 4 h were incubated. Finally, MTT solutions were removed and DMSO (200 μL) were added to each well and by spectrophotometer (BioTek Instruments, Inc., Bad Friedrichshall, Germany) the absorbance at 570 nm was read ( Heidari Majd et al, 2017 ; Moghaddam‐manesh et al, 2021 ; Moghaddam‐Manesh and Hosseinzadegan, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…the cells were treated with concentrations of 6.25 μM/ml, 12.5 μM/ml, 25 μM/ml, 75 μM/ml, 150 μM/ml, and 300 μM/ml of Y-MOF and pyrazolopyranopyrimidines derivatives for 48 h. After 48 h, the media from the well were removed and added 150 μL of fresh media plus 50 μL of MTT solutions (prepared as 2 mg/ml in PBS) and for 4 h were incubated. Finally, MTT solutions were removed and DMSO (200 μL) were added to each well and by spectrophotometer (BioTek Instruments, Inc., Bad Friedrichshall, Germany) the absorbance at 570 nm was read ( Heidari Majd et al, 2017 ; Moghaddam‐manesh et al, 2021 ; Moghaddam‐Manesh and Hosseinzadegan, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Antimicrobial activity, including antibacterial and antifungal, against Gram-positive, Gram-negative, and specialized aquatic bacterial species was performed based on CLSI (Clinical and Laboratory Standards Institute) methods (Etemadi et al, 2016;Moghaddam-Manesh et al, 2020;Moghaddam-Manesh and Hosseinzadegan, 2021).…”
Section: Antibacterial and Antifungal Methodsmentioning
confidence: 99%
“…The microplate containing the mixtures were placed in an incubator set at right temperature (for bacterial species: 37 °C; for fungal species 27 °C) for 48 h. Clear wells indicate the lack of bacterial growth, and turbid wells indicate bacterial growth at that concentration. The first well from which transparency started was reported as the minimum inhibitory concentration (Etemadi et al, 2016;Moghaddam-Manesh et al, 2020;Moghaddam-Manesh and Hosseinzadegan, 2021).…”
Section: Mic Valuementioning
confidence: 99%
“…Anticancer activity studies of CCPSF NPs using the MTT method and previously reported on MCF-7 breast cancer cells were done. The densities of 1.2 × 10 4 (cells/well) MCF-7 breast cancer cells for 24 and 48 h in concentrations of 5, 10, 20, 40, 80, 120, and 200 mg/ml CCPSF NPs were tested ( Moghaddam-Manesh and Hosseinzadegan, 2021 ).…”
Section: Methodsmentioning
confidence: 99%